دور تطبيقات الذكاء الاصطناعي في تحسين خدمات الصيرفة الالكترونية - حمودي امال; عوينان عبد القادر (جامعة الوادي University of Eloued, 2024)
This study seeks to examine the role of artificial intelligence in elevating electronic banking services, set against the backdrop of rapid and transformative shifts witnessed across numerous sectors globally. The acceleration in contemporary technological advancements has enabled the development of new, sophisticated approaches to delivering banking services, giving rise to a suite of AI-driven applications designed to enhance digital banking performance. By examining this dynamic within the National Popular Credit Bank, the study identified key findings: the bank’s integration of electronic banking has played a notable role in enhancing its service offerings, including e-banking solutions, online payments, and Mobile CPA services. Furthermore, electronic banking provides a range of accessible channels for conducting transactions, such as ATMs. Nonetheless, the study highlighted a critical gap — the limited presence of fourth-generation technology applications, particularly artificial intelligence, within the bank’s operational framework.
The role of artificial intelligence applications in improving electronic Banking services CPA
Keywords: ذكاء اصطناعي; صيرفة إلكترونية; صراف آلي; بطاقة الدفع; Artificial intelligence; electronic banking; payment card